Exposure to DMSO during infancy alters neurochemistry, social interactions, and brain morphology in long‐evans rats. Issue 5 (10th April 2021) - Rabow, Zachary; Morningstar, Taryn; Showalter, Megan; Heil, Hailey; Thongphanh, Krista; Fan, Sili; Chan, Joanne; Martínez‐Cerdeño, Verónica; Berman, Robert; Zagzag, David; Nudler, Evgeny; Fiehn, Oliver; et al.
Abstract: Introduction: Dimethyl sulfoxide (DMSO) is a widely used solvent to dissolve hydrophobic substances for clinical uses and experimental in vivo purposes. While usually regarded safe, our prior studies suggest changes to behavior following DMSO exposure. We therefore evaluated the effects of a five‐day, short‐term exposure to DMSO on postnatal infant rats (P6‐10). Methods: DMSO was intraperitoneally injected for five days at 0.2, 2.0, and 4.0 ml/kg body mass. One cohort of animals was sacrificed 24 hr after DMSO exposure to analyze the neurometabolic changes in four brain regions (cortex, hippocampus, basal ganglia, and cerebellum) by hydrophilic interaction liquid chromatography. A second cohort of animals was used to analyze chronic alterations to behavior and pathological changes to glia and neuronal cells later in life (P21‐P40). Results: 164 metabolites, including key regulatory molecules (retinoic acid, orotic acid, adrenic acid, and hypotaurine), were found significantly altered by DMSO exposure in at least one of the brain regions at P11 ( p  < .05). Behavioral tests showed significant hypoactive behavior and decreased social habits to the 2.0 and 4.0 ml DMSO/kg groups ( p  < .01). Significant increases in number of microglia and astrocytes at P40 were observed in the 4.0 ml DMSO/kg group (at p  < .015.) Conclusions: Despite short‐term exposure at low, putatively nontoxic concentrations, DMSO led to changes in behavior and social preferences, chronic alterations in glial cells, and changes in essential regulatory brain metabolites. The chronic neurological effects of DMSO exposure reported here raise concerns about its neurotoxicity and consequent safety in human medical applications and clinical trials. Abstract : Summary of cellular and metabolic brain changes following brief exposure to DMSO.